The Cossack Economy in the Context of Developing Urban Environment on the Cusp of the XIX-XX Centuries (Based on the Data Provided by the Siberian Researcher G.Ye. Katanayev) - Mukatayeva, L.K. (KU Publ., 2021)
This article is devoted to examining the peculiarities of the Cossack land use in the context of the emerging urban environment. The cities of pre-revolutionary Kazakhstan are notable for a number of specific features, such as the poor development of the urban lifestyle, urban infrastructure, and urban economy, based mainly on agriculture. Uniqueness of urban construction on the national outskirts of the Russian Empire, including the north of Kazakhstan, consisted in the weak distinction between a city and a rural settlement, which was due to evolution of serf localities into the later urban ones. The Cossacks played a significant role in the formation of the urban environment, reserving the right to the closed nature of their class and the opportunity to be engaged in traditional ways of economy. The G.Ye. Katanayev treatise “The Kirghiz Issue in the Siberian Cossack Army” published in 1904 is a valuable source of history of the economic development of the city and the steppe, contacts with the Cossacks and peasant settlers. The Siberian historian, having carefully investigated the problems of land management of the Cossacks, seeks not only to justify their way of life but also to make the disputed territories legitimate for them. Issues of land relations addressed the interests of the local population that are shown in the book as observations and some recommendations of the ideologist of the Cossack army. The work deals with reasons and consequences of creating the “ten-verst corridor” by the tsarist administration in order to further allot the Irtysh riverfront to the Cossacks. The book also comprises the facts of cultural interaction between the Kazakh ethnic group and the Cossacks of the Siberian Cossack Army. The author of the article also draws upon the researches preceding the main one used and archival materials of the Historical Archive of the Omsk Region. Considering the problems of land development is important for covering the issues related to the settlement, reclamation of Siberia and the legal confirmation of these processes.
XIX-XX ғасырлар шегіндегі дамып келе жатқан қалалық орта жағдайындағы казактар шаруашылығы (Сібір зерттеушісі Г.Е.Катанаевтың материалдары негізінде)
Keywords: Cossackdom; land issue; land lease; contacts of the Kazakhs and Cossacks; urban environment